The Influence of Work Motivation on Employee Performance with Organizational Commitment as a Mediating Variable - Alberd Alberd; Muhammad Irfani Hendri; Maria Christiana Iman Kalis (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Employee performance is crucial for organizational success, and understanding the factors that influence it is essential. This study examines the influence of work motivation on employee performance, with organizational commitment serving as a mediating variable. This study employed a quantitative research method. The research population consisted of 49 managers, and saturated sampling was used to collect data from all respondents via structured questionnaires. Data were analyzed using WarpPLS version 7.0. The findings reveal that work motivation has a non-significant direct effect on employee performance, while it has a positive and significant impact on organizational commitment. In turn, organizational commitment positively and significantly influences employee performance. Furthermore, organizational commitment effectively mediates the relationship between work motivation and employee performance, highlighting its critical role in translating motivation into improved performance outcomes. These results suggest that enhancing organizational commitment is essential for ensuring that employee motivation contributes meaningfully to performance. The study provides practical insights for management in designing targeted strategies to strengthen both motivation and commitment, ultimately fostering higher levels of employee performance in the organization.